A Byzantine shipwreck from Kasos Island (Greece): the ceramic evidence - Argiris , Xanthie (Journal of Greek Archaeology, 2024)
Between 2019-2024 the Institute of Historical Research (IHR) of the National Hellenic Research Foundation in collaboration with the Ephorate of Underwater Antiquities (EUA) conducted an underwater archaeological survey in the waters of Kasos Island. The aim of the Kasos Maritime Archaeological Project (KMAP) is to locate and document ancient to Early-Modern shipwrecks, harbors, and submerged architectural remains, but also isolated ceramic, and other finds attempting to understand and assess maritime networks and hierarchies in the southern Aegean through time. Kasos is one of the smaller islands of the Dodecanese. It is located on the south-eastern part of the Aegean, next to the far larger Karpathos Island, between Rhodes and Crete.